THE INTRAPERSONAL FIELD OF SOCIO-EMOTIONAL INTELLIGENCE. FROM SELF-KNOWLEDGE TO EMOTION MANAGEMENT - Mihaela Aurelia ȘTEFAN (Universitaria Publishing House, Craiova, 2022)
Research shows that emotional intelligence provides a variety of useful acquisitions during one's life. Higher EQ levels are associated with an increased likelihood of inner balance and positive interactions with others. The study aims to address the intrapersonal dimension of emotional intelligence, namely the relationship with ourselves, with an emphasis on selfknowledge, self-awareness of emotions, emotions representing the link between thought, feeling and action. The proposed experimental program aimed at carrying out counseling activities focused on self-knowledge, on developing a clear and correct self-image. The research data showed that counseling activities cause positive changes in attitudes: self-confidence, optimism, enthusiasm.